21st Century Socialism - Cadena Hermosa, Carlos (2010)
As a trend, the socialism of the 21st century made its appearance at the end of the last century, as a reformulation of the Marxist theory that incorporates elements of the new current economic models, a conception that has spread strongly in several Latin American countries, with Venezuela at the head of the process. However, the actions that can be implemented under this model can be more considered trials, the results of which will depend on the way they are applied in each country and the social acceptance they may have among citizens.